Study on anticorrosion properties of epoxy primers on steel - Huy Cuong, Huynh Le; Dieu, Tran Vinh; Thanh, Nguyen Dac; Yen Oanh, Doan Thi (Vietnam Journal of Chemistry, 2016)
Epoxy resin DER 671X75 was reinforced by nanoclay cloisite 30B with content of 2% and primer coatings based on epoxy resin DER 671X75 were formed with pigments, fillers. Epoxy coating films were exposed by electrochemical method in NaCl 3.5 % solution in 28 days and salt spray accelerated tester in 330 hrs. The results show that nanoclay cloisite 30B are improved anticorrosion properties of primer coatings based on epoxy resin DER671X75. Keywords. Epoxy primer coating, nanoclay cloisite 30B, epoxy resin DER 671X75, electrochemical, anticorrosion properties steel.